Self Care Management Berhubungan dengan Kualitas Hidup pada Penderita Hipertensi - Ayuningjati, Krisma Giri; Rosyid, Fahrun Nur (Journal of Telenursing (JOTING), 2024)
This study aims to determine the relationship between self-care management and quality of life in hypertension sufferers. This research uses a cross-sectional approach, where independent and dependent variable data are observed only once, with no follow-up. The research results based on the chi-square test obtained p-value = 0.000 < 0.05, which means there is a relationship between self-care management and the quality of life of hypertension sufferers. In conclusion, the results obtained from this research show a relationship between self-care management and quality of life in hypertension sufferers. Keywords: Hypertension, Quality of Life, Self Care Management